Iterative Implementation of a Remote Cardiac Patient Monitoring Device using Qualitative Analysis and Human Factors Engineering. (September 2017) - Lowndes, Bethany R; Finnie, Dawn; Hathaway, Julie; Ridgeway, Jennifer L.; Vickers-Douglas, Kristin; Bruce, Charles; Hallbeck, M. Susan
Remote monitoring has the potential to improve patient care and satisfaction while reducing the cost of care and burden on the healthcare system for Congestive Heart Failure (CHF) and Atrial Fibrillation (AF) patients. However, the device must be convenient and easy for the population to use correctly. In this study, human factors and qualitative researchers evaluated the use of a remote cardiac monitoring device during a clinical trial with 74 CHF and AF patients. Human factors usability concerns centered on device use and the information presented in the manual. The key themes identified during the qualitative analysis were related to patient education. These findings were incorporated into device design, user manual, or education material updates. This study illustrates how these methods can infuse patient experience into device design to inform continued quality improvement and usability refinement specifically in devices to aid CHF and AF patients without added burden.